Linguistic performance of dual language immersion students. (14th August 2018) - Watzinger‐Tharp, Johanna; Rubio, Fernando; Tharp, Douglas S.
Abstract : The assessment of dual language immersion (DLI) students' proficiency in the partner language plays a key role in program evaluation. This article reports findings from a large‐scale study, drawing on cross‐sectional assessment data from 73 schools and longitudinal data from 25 schools. Students were tested in the interpretive (listening and reading) and interpersonal (listening/speaking) modes of communication, using the ACTFL Assessment of Proficiency Towards Performance in Languages. The cross‐sectional analysis shows that French and Spanish students performed at Intermediate Low across skills in fourth or fifth grade and Intermediate Mid in sixth grade. Sixth‐grade Chinese DLI students attained near Intermediate Mid in listening and Novice High to Intermediate Low in reading and speaking. Across languages, students achieved the highest ratings in listening and, overall, performed more strongly in listening and reading than speaking. A regression analysis of students' change scores over time revealed significant progress in nearly all tested skills and languages. Baseline scores and partner language (Chinese, French, or Spanish) accounted for significant variation in growth rates; between‐school differences were found not to be significant. The article discusses implications for assessment instruments and DLI policy and also addresses some instructional implications. The Challenge: Research has shown that dual language immersion students perform as well as their monolingual peers in English and math. Our study focuses on partner language proficiency. How well do dual language immersion students read, listen, and speak in Chinese, French, and Spanish? Are they progressing toward the ultimate goal of bilingualism and biliteracy?